Theoretical Basics of Ensuring Food Security of the Country - Samiyeva Gulnoza; Ochilova Maftuna (Research Parks Publishers, 2022)
The article reveals the importance of ensuring food safety and the practical aspects of consistent reforms in this regard in our country.